STUDI PEMANFAATAN ROTAN OLEH MASYARAKAT DESA LANDAU MENTAIL KECAMATAN BOYAN TANJUNG KABUPATEN KAPUAS HULU - Handayani, Yusi; Hardiansyah, Gusti; Idham, M (Universitas Tanjungpura, 2019)
Rattan is a non-timber forest product that lives and grows in tropical forest and is very suitable for planting in Indonesia. Landau-Mentail village has the potential of abundant forest products which can be seen from its forest that have not yet been used as settlements, however, the potential of the forest in this village is not properly by the community due to a lack of community interest in processing forest products. This research is to get information on how people use rattan and how manny products they produce and describe the increase in income that people get from the result of rattan products. The method used is descriptive method with survey techniques in Landau-Mentail Village. The result of the study showed that people used rattan to be waven, there were 4 woven products that the community produces can increase revenue by 43.96% of total income of respondents who sell their wicker to the market.Keyword: Rattan, Community, Income, Landau Mentail Village